Digital Branding–Based Transformation of DNA Crab MSMEs to Enhance Local Product Competitiveness (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
MSMEs DNA Crab is one of the potential Micro, Small, and Medium Enterprises (MSMEs) that focuses on collecting (supplier) and developing mangrove crabs located in Blacanan Village, Siwalan District, Pekalongan Regency, Central Java. Through this community service program, MSMEs DNA Crab is assisted in the digital transformation process to increase the competitiveness of local products.  The objective of this activity is to create an effective digital branding strategy through innovative visual media-based promotion and the use of communicative language. One form of digital transformation that has been carried out is the creation of MSMEs' profile videos that showcase the business process, product advantages, and the story behind the brand as a form of attractive visual promotion. The methods used include surveys, field observations, in-depth interviews with partners, as well as literature studies from various previous references, training, and mentoring. The results show an increase in digital literacy among MSME players, the creation of structured visual branding assets, such as e-catalogues, branding videos, and the launch of online promotion platforms, which indicate that local products are better prepared to compete in the digital market.